Review of synthetic human faeces and faecal sludge for sanitation and wastewater research. (1st April 2018) - Penn, Roni; Ward, Barbara J.; Strande, Linda; Maurer, Max
Abstract: Investigations involving human faeces and faecal sludge are of great importance for urban sanitation, such as operation and maintenance of sewer systems, or implementation of faecal sludge management. However, working with real faecal matter is difficult as it not only involves working with a pathogenic, malodorous material but also individual faeces and faecal sludge samples are highly variable, making it difficult to execute repeatable experiments. Synthetic faeces and faecal sludge can provide consistently reproducible substrate and alleviate these challenges. A critical literature review of simulants developed for various wastewater and faecal sludge related research is provided. Most individual studies sought to develop a simulant representative of specific physical, chemical, or thermal properties depending on their research objectives. Based on the review, a suitable simulant can be chosen and used or further developed according to the research needs. As an example, the authors present such a modification for the development of a simulant that can be used for investigating the motion (movement, settling and sedimentation) of faeces and their physical and biological disintegration in sewers and in on-site sanitation systems. Graphical abstract: Image 1 Highlights: We review synthetic human faeces and faecal sludge for sanitation related research. Making use of these simulants can make research more reproducible and safer. Simulants represent specific properties depending on the research objectives. Simulants can be modified to meet emerging research needs. We give an example. Characterization of faeces and faecal sludge is needed to validate simulants.